2015
DOI: 10.1016/j.ajog.2014.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of adverse events after uterosacral colpopexy for uterovaginal and posthysterectomy vault prolapse

Abstract: OBJECTIVE:We sought to describe perioperative and postoperative adverse events associated with uterosacral colpopexy, to describe the rate of recurrent pelvic organ prolapse (POP) associated with uterosacral colpopexy, and to determine whether surgeon technique and suture choice are associated with these rates. STUDY DESIGN:This was a retrospective chart review of women who underwent uterosacral colpopexy for POP from January 2006 through December 2011 at a single tertiary care center. The electronic medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 28 publications
(29 reference statements)
3
26
0
1
Order By: Relevance
“…30,33,34 In our population, the use of D10 was associated with a 22% increase in UTI with a number needed to harm of 4.5 (absolute rate in D10 group of 47.8%). Patients whose cystoscopy was performed with D10 had a 3.4 times greater odds of being treated for a UTI in the 6 weeks following surgery, even after adjusting for a history of prolonged postoperative catheterization and preoperative recurrent UTI, which are among the most modifiable risk factors of postoperative UTI in patients undergoing urogynecological procedures.…”
Section: Commentmentioning
confidence: 71%
See 2 more Smart Citations
“…30,33,34 In our population, the use of D10 was associated with a 22% increase in UTI with a number needed to harm of 4.5 (absolute rate in D10 group of 47.8%). Patients whose cystoscopy was performed with D10 had a 3.4 times greater odds of being treated for a UTI in the 6 weeks following surgery, even after adjusting for a history of prolonged postoperative catheterization and preoperative recurrent UTI, which are among the most modifiable risk factors of postoperative UTI in patients undergoing urogynecological procedures.…”
Section: Commentmentioning
confidence: 71%
“…In a retrospective chart review of 983 women who underwent uterosacral colpopexy for pelvic organ prolapse between January 2006 and December 2011, the overall rate of UTI was 20.3% (95% confidence interval [CI], 17.9e23.6). 30 Presuming a 20% baseline UTI rate in our control group and a fixed sample size of 110 patients in the D10 arm and 180 patients in the NS arm, this study had 80% power to detect an absolute increase of 15% in the UTI rate. We used PASS 11 software ajog.org GYNECOLOGY Original Research from NCSS (Kaysville, UT) to perform our power analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that a mesh repair of POP in only one compartment leads to a significantly higher percentage of clinically relevant de novo prolapse of the untreated vaginal compartment [15,16]. Sacropexy, which is considered the most durable procedure for advanced POP, in the long term demonstrated failure in the anatomical support [17] with a recurrent POP rate of 14.4%, requiring surgery in 3.4% of cases [18]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the laparoscopic high uterosacral ligament suspension (LHULS) has shown good anatomic outcome for vault prolapse [9][10][11][12]. Interestingly, this procedure does not require any graft, therefore, the concerns about the graft-related complications are dispelled [11].…”
Section: Introductionmentioning
confidence: 99%